THE RELATIONSHIP BETWEEN FAMILY SUPPORT AND MEDICATION COMPLIANCE IN MENTAL DISORDER PATIENTS - Wijayanti, Endah Sri; Mukti, Doni Karisma; Iswatun, Iswatun; Fadliyah, Lailatul; Umam, Khotibul; Susanto, Joko (Universitas Airlangga, 2025)
Introduction: Patients with mental disorders who receive rehabilitation at home or as outpatients require support to comply with their treatment programs. One of the significant barriers to improving the health status of these patients is non-compliance with prescribed medications. This study aims to determine the relationship between family support and medication compliance in patients with mental disorders within the working area of the Turi Lamongan Health Center. Methods: This is an analytical study with a cross-sectional approach. The study population consisted of 90 families of patients with mental disorders, with a sample size of 73 respondents. Simple Random Sampling was used as the sampling technique. Data were collected using a questionnaire. The statistical test applied was Spearman's Rank correlation, with α = 0.05. Results: Among the 73 respondents, most reported moderate family support, with 38 respondents (52.1%), while a smaller proportion reported poor support, with 12 respondents (16.4%). Regarding medication compliance, most respondents showed moderate compliance, with 36 respondents (49.3%), and a smaller proportion exhibited good compliance, with 10 respondents (13.7%). The results of the Spearman Rank test revealed a ρ-value of 0.000 < α = 0.05, and the calculated r-value was 0.671. Conclusions: There is a significant relationship between family support and medication compliance in patients with mental disorders in the Turi Lamongan Health Center work area, with a strong degree of association.